2017
DOI: 10.1017/s1751731116001294
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA508-3p in melanogenesis by targeting microphthalmia transcription factor in melanocytes of alpaca

Abstract: It has been demonstrated that microRNAs (miRNAs) play important roles in the control of melanogenesis and hair color in mammals. By comparing miRNA expression profiles between brown and white alpaca skin, we previously identified miR508-3p as a differentially expressed miRNA suggesting its potential role in melanogenesis and hair color formation. The present study was conducted to determine the role of miR508-3p in melanogenesis in alpaca melanocytes. In situ hybridization showed that miR508-3p is abundantly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Besides, miR-25 inhibited the production and the secretion of SCF and bFGF from keratinocytes, thus inhibiting their paracrine effect on the survival of melanocytes under oxidative stress [128]. A second study in the Alpaca identified miR-508-3p as a regulator of melanogenesis via direct MITF targeting [129]. Finally, the microRNA miR-nov-66 was also identified as involved in melanogenesis, as miR-nov-66 overexpression in Alpaca melanocytes was followed by the downregulation of MITF, TYR and TYRP1 [130].…”
Section: Micrornas Targeting Mitfmentioning
confidence: 99%
“…Besides, miR-25 inhibited the production and the secretion of SCF and bFGF from keratinocytes, thus inhibiting their paracrine effect on the survival of melanocytes under oxidative stress [128]. A second study in the Alpaca identified miR-508-3p as a regulator of melanogenesis via direct MITF targeting [129]. Finally, the microRNA miR-nov-66 was also identified as involved in melanogenesis, as miR-nov-66 overexpression in Alpaca melanocytes was followed by the downregulation of MITF, TYR and TYRP1 [130].…”
Section: Micrornas Targeting Mitfmentioning
confidence: 99%
“…Numerous miRNAs have been reported to be involved in the regulation of melanogenesis [5], and these miRNAs include miR-137, miR-434-5p, miR-218, miR-21a-5p, miR-145, miR-340 and miR-27a-3p [612]. We have demonstrated that miR-508-3p [13] and miR-25 [14] regulate melanogenesis by targeting MITF in alpaca melanocytes. miR-143-5p regulates alpaca melanocyte migration, proliferation, and melanogenesis [15]; miR-5110 regulates eumelanin production and transfer in alpaca ( Vicugna pacos ) melanocytes by cotargeting melanophilin (MLPH) and Wnt family member 1 (Wnt1) [16]; and lpa-miR-nov-66 targeting of soluble guanylate cyclase (sGC) regulates melanogenesis via the cyclic adenosine monophosphate (cAMP) pathway [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports on the cellular and molecular responses of osmoregulatory enzymes have been published under acute and long term salinity stress conditions in Scylla paramamosain , black tiger shrimp, white shrimp, green crab, killifish, and hermit crab (Chung and Lin 2006; de la Vega et al 2007; Gao et al 2012; Henry et al 2006; Scott et al 2005; Rhodes-Ondi and Turner 2010). The study in oysters showed that ion channels play important roles in oysters under short- and long-term hypoosmotic stress (Zhang et al 2016). The studies indicated that oysters, as successful colonizers of intertidal zones and estuaries, are remarkably resilient against harsh salinity fluctuations (Guo et al 2015).…”
Section: Introductionmentioning
confidence: 99%